2015
DOI: 10.1093/intqhc/mzv019
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards vital signs monitoring in the detection of clinical deterioration: scale development and survey of ward nurses

Abstract: This exploratory study provides evidence for the psychometric properties of the V-scale. It reveals a need for continuous professional development to improve ward nurses' attitudes towards vital signs monitoring. Vital signs monitoring needs to be prioritized in workload planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
117
0
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(137 citation statements)
references
References 26 publications
7
117
0
13
Order By: Relevance
“…In congruence with a previous study,2 reliance on technology was highlighted as a barrier to the use of nursing assessment skills. The use of electronic vital signs monitoring not only minimises nurse–patient contact time but also reduces the time nurses spend on sensory skills assessment.…”
Section: Commentarysupporting
confidence: 85%
“…In congruence with a previous study,2 reliance on technology was highlighted as a barrier to the use of nursing assessment skills. The use of electronic vital signs monitoring not only minimises nurse–patient contact time but also reduces the time nurses spend on sensory skills assessment.…”
Section: Commentarysupporting
confidence: 85%
“…Issues with the recording of vital signs and the activation of rapid response systems have long been acknowledged 4. Assessment of respiratory rates, even though essential, is typically neglected by nursing staff, perhaps because of over-reliance on oxygen saturation levels 2. This study has demonstrated that providing a relatively short educational intervention can improve the monitoring of vital signs and the communication of abnormalities by enrolled nurses.…”
Section: Commentarymentioning
confidence: 86%
“…While the decision to escalate care remains the responsibility of the assigned registered nurse, enrolled nurses are in close contact with patients at the bedside. They provide surveillance that is essential to ensure timely recognition of altered vital signs and other symptoms that may precede unplanned intensive care unit admission or death 2. This study is in alignment with a movement within the nursing profession to share the responsibility of recognising a deteriorating patient.…”
Section: Commentarymentioning
confidence: 94%
“…1) making it difficult for staff to monitor the event on foot and to aid in emergencies. In addition, public and charity competitions in many countries do not usually require health checks prior to events, therefore increasing the risk for cardiac-related injuries [5][6][7][8][9][10][11][12][13] and other injury types [14][15][16][17][18]. Furthermore, this particular sport is open to individuals of all ages, some having hearing impairments which may cause additional difficulties in communicating during an emergency.…”
Section: Introductionmentioning
confidence: 99%